Investigating Neurocranial Sizes And Cephalic Indices Of Male Newborns In North of Tehran Using Millimetric Cephalometry - Soltani, Reza; Aghajanpour, Fakhroddin; Shahrbaf, Mohammad Amin; Pouriran, Ramin; nourozian, Mohsen; Fadaei, Fatemeh; Abbaszadeh, Hojjat-Allah; Mastery Farahani, Reza (Student Research in Translational Medicine, 2019)
Background: Anthropometric studies have been introduced as the second priority of research in the field of medical sciences in Iran. Information obtained from such studies are used in industry and medical sciences, including the manufacturing of prostheses, gas masks, and surgical instruments. Considering the effect of genetic, age, sexual, climatic, and geographical factors and their high importance on anthropometric sizes, the aim of the present project is to investigate the neurocranial sizes of the cephalic indices of one-day-old male newborns in north of Tehran. Materials and Methods: This cross-sectional descriptive study was carried out on 100 neurocranial sizes of one-day-old male newborns in Shohada-e-Tajrish Hospital in Tehran using millimetric cephalometry. Measurements were performed according to the protocol and by a ruler, cephalometer, and tape meter (0.5mm precision rate). The data were collected and recorded in the relevant forms and then processed and analyzed by a biostatistics software. Results: The present research showed that the mean head length, head width, ear height, head circumference, brain volume, brain weight, cephalic index, and the brain index was 118.2 mm, 94.3 mm, 71.3 mm, 348.5 mm, 415.1 ml, 429.2 g, 78.1%, and 12.8%, respectively. Frequency of different head phenotypes has been reported according to the cephalic index as follows: round head (65%), long head (20%), broad head (12%), and super-broad head (3%). Conclusion: The results of the present study showed that the cephalic index of one-day-old male newborns in Tehran was lower than those born in Kermanshah, Sistan and Baluchestan, and Qazvin, which can be explained by the impact of gender, climate, and geographical area on neurocranial dimensions and sizes.